(untitled) (Research, Society and Development, 2022)
Introduction: Aplastic anemia (AA) is the deficiency of the production of blood cells, with pancytopenia and hypocellular marrow as a result. Eltrombopag® (EPAG), a synthetic thrombopoietin mimic, showed improvement in bone marrow, CD34 and blood precursor cell counts. Today, it is indicated as first-line therapy, in addition to Immunosuppressive Therapy (IST) with cyclosporine and horse Antithymocyte Globulin (ATG). The aim of this study is to compare costs and results of the main current therapeutic schemes for AA among young individuals. Method: This is a study to estimate costs and results of a therapeutic scheme using EPAG associated with IST and the management of complications in comparison with standard therapy. The protocols used were those of the Ministry of Health and the scheme indicated in the literature for the EPAG. As a basis for calculation, a typical patient was simulated, who would be followed up by a pediatric hematology service in Sergipe, which works as part of the Unified Health System. Result: The cost of Cyclosporine + rabbit ATG treatment for 6 months, based on patient weight, was US4500. The cost of Cyclosporine + rabbit GAT + EPAG treatment for 6 months was US182,000. Conclusion: It is concluded, therefore, that drug therapy with EPAG increases the cost of treatment by 40 times. Several studies, however, point to clinical and laboratory gains and increased response rates to the proposed therapy, thus contributing to a better quality of life for a pediatric patient with AA.